On the Origin of Water Masses in the Beaufort Gyre. Issue 7 (9th July 2019) - Kelly, S. J.; Proshutinsky, A.; Popova, E. K.; Aksenov, Y. K.; Yool, A.
Abstract: The Beaufort Gyre is a key feature of the Arctic Ocean, acting as a reservoir for freshwater in the region. Depending on whether the prevailing atmospheric circulation in the Arctic is anticyclonic or cyclonic, either a net accumulation or release of freshwater occurs. The sources of freshwater to the Arctic Ocean are well established and include contributions from the North American and Eurasian Rivers, the Bering Strait Pacific water inflow, sea ice meltwater, and precipitation, but their contribution to the Beaufort Gyre freshwater accumulation varies with changes in the atmospheric circulation. Here we use a Lagrangian backward tracking technique in conjunction with the 1/12‐degree resolution Nucleus for European Modelling of the Ocean model to investigate how sources of freshwater to the Beaufort Gyre have changed in recent decades, focusing on increase in the Pacific water content in the gyre between the late 1980s and early 2000s. Using empirical orthogonal functions we analyze the change in the Arctic oceanic circulation that occurred between the 1980s and 2000s. We highlight a "waiting room" advective pathway that was present in the 1980s and provide evidence that this pathway was caused by a shift in the center of Ekman transport convergence in the Arctic. We discuss the role of these changes as a contributing factor to changes in the stratification, and hence potentially the biology, of the Beaufort Gyre region. Plain Language Summary: The Beaufort Gyre, a clockwise ice and water circulation in the Arctic Ocean, is an important feature of the Arctic because it stores a large volume of fresh—relative to the rest of the ocean—water. Depending on the atmospheric circulation driving it, the Beaufort Gyre can either accumulate or release this freshwater. The sources of relatively freshwater to the Beaufort Gyre are Arctic rivers, the Bering Strait, and melting sea ice. By tracking virtual particles in a high‐resolution ocean model, we investigate how these sources have changed in recent decades, and identify a change in the pathways bringing them to the Beaufort Gyre. This change in ocean circulation was found to correlate with a change in the mixed layer depth in the model. Key Points: Lagrangian particle tracking technique used to investigate advective pathways associated with different sources of Beaufort Gyre water Change in advective pathways associated with Pacific inflow to the gyre occurred between 1980s and 2000s This change in pathways correlates with a shoaling of the modeled mixed layer depth in the Beaufort Gyre region